Segmental and Suprasegmental Mispronunciations Made by EFL Learners in Indonesia - Maulana Rahman Firdaus; A. Dzo'ul Milal (English Department, Faculty of Humanities, Andalas University, 2021)
This study reveals segmental and suprasegmental mispronunciations of some words made by Indonesian learners of EFL and their possible causes. This is descriptive qualitative research. The phonological data were elicited by asking the subjects to read loudly while recorded the text that had been prepared to contain words with segmental and suprasegmental phonemes. The data were limited to those words existing in the eliciting text. The records were then transcribed, identified, coded, classified, and interpreted. The possible causes that might have influenced the mispronunciations made by the subjects were unfolded using the contrastive analysis approach and psycholinguistic theories. The study reveals that the mispronunciations in segmental phonemes include vowels and diphthongs, such as /i:/, /ɑ:/, /eɪ/, /oʊ/, consonants /z/, /v/, /ð/, and silent letters w, l, and s. The suprasegmental mispronunciations are in the use of stress on multi-syllabic words. Finally, this study concludes the possible causes that made these errors happen, among others, are interlingual differences, mother tongue interference, shortage of knowledge, and fossilization.